When Our Work Hits Home: Trauma and Mental Disorders in Correctional Officers and Other Correctional Workers - Fusco, Nina; Ricciardelli, Rosemary; Jamshidi, Laleh; Carleton, R. Nicholas; Barnim, Nigel; Hilton, Zoe; Groll, Dianne (Frontiers in Psychiatry, 2021)
Background: International estimates suggest that up to one in three public safety personnel experience one or more mental disorders, including posttraumatic stress disorder (PTSD). Canadian data have been sparse until very recently, and correctional officers and forensic psychiatric staff have rarely been included. Working as a correctional officer is associated with negative health outcomes and increased work-related stress, with several variables affecting reported levels of stress (Dowden & Tellier, 2004). Healthcare staff also report higher rates of PTSD, especially those who are exposed to aggression in their workplace (Hilton et al., 2017). In the present study, we compare current symptoms of diverse staff working in correctional occupations. Method: Data were collected from a Canadian national online survey of public safety personnel, including employees of correctional services at the federal level. Correctional officers and wellness services staff were compared for prevalence of mental disorders and suicidal ideation. Results: Correctional officers self-reported statistically significantly more exposure to potentially psychologically traumatic events than wellness services employees. Correctional officers also self-reported higher rates of symptoms of mental disorders, including PTSD, social anxiety, panic disorder, and depression. There were no statistically significant differences in reports of suicidal thoughts, plans, or attempts. Contribution to Society: Correctional and forensic staff contribute to society by working with justice-involved individuals in correctional institutions. Trauma-related disorders and other mental health problems threaten the well-being of correctional and forensic staff. Mental health likely impacts the ability of correctional and forensic staff to develop a therapeutic or working alliance with persons in custody. Staff well-being must be recognized and addressed to ensure that prisoners and staff receive optimal treatment in prison. Conclusion: Our results add to the limited knowledge about the well-being of staff, particularly wellness staff in prisons, who provide daily treatment and care for prisoners with serious mental disorders. Our work is a step towards identifying avenues for promoting staff well-being.